2022
DOI: 10.1056/nejmoa2117608
|View full text |Cite
|
Sign up to set email alerts
|

Final Analysis of Efficacy and Safety of Single-Dose Ad26.COV2.S

Abstract: Background The Ad26.COV2.S vaccine was highly effective against severe–critical coronavirus disease 2019 (Covid-19), hospitalization, and death in the primary phase 3 efficacy analysis. Methods We conducted the final analysis in the double-blind phase of our multinational, randomized, placebo-controlled trial, in which adults were assigned in a 1:1 ratio to receive single-dose Ad26.COV2.S (5×10 10 viral particles) or placebo. The primary end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
223
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(229 citation statements)
references
References 22 publications
5
223
0
1
Order By: Relevance
“…Increased secondary attack rate. Unknown Unknown 70.4% 261 70.2% 262 85.6% 262 1.2-fold decrease of neutralizing antibody titers 263 89.5% 264 B.1.351 (Beta) 5.2 Possible increased risk of severe disease and in-hospital mortality. Two-dose: 5.47-fold decrease of plasma neutralization titers compared to against prototype.…”
Section: Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
“…Increased secondary attack rate. Unknown Unknown 70.4% 261 70.2% 262 85.6% 262 1.2-fold decrease of neutralizing antibody titers 263 89.5% 264 B.1.351 (Beta) 5.2 Possible increased risk of severe disease and in-hospital mortality. Two-dose: 5.47-fold decrease of plasma neutralization titers compared to against prototype.…”
Section: Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
“…However, protection against COVID-19 infection appeared to wane over time with Ad26.COV2.S demonstrating the most prominent decrease from 75% to 60% protective efficacy 5 months after vaccination, compared to a decrease in vaccine efficacy from 95% to either 67% or 80% after BNT162b2 and mRNA-1273 vaccination, respectively, over a similar period of time ( 4 ). Loss of protection against infection was associated with lower overall levels of SARS-CoV-2 spike protein (S)–specific antibodies and plasma neutralizing activity after Ad26.COV2.S immunization compared to mRNA vaccines ( 5, 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…1.351) and Delta (B.1.617.2) variants of concern (VOC) were initially thought to potentially evade vaccine elicited immunity. However, COVID-19 vaccine efficacy was largely maintained [3][4][5][6][7][8] . The Delta VOC obtained virtually worldwide dominance until it was replaced by the Omicron variant, BA.1 (initially named B.1.1.529).…”
Section: Introductionmentioning
confidence: 99%
“…Janssen developed the Ad26.COV2.S vaccine, which is a replication-incompetent human adenovirus type 26 (Ad26) vector 1 encoding a stabilized pre-fusion SARS-CoV-2 spike protein based on the Wuhan-Hu-1 isolate 2 . A phase 3 trial demonstrated that Ad26.COV2.S was 74.6% efficacious at preventing severe-critical COVID-19 3 . The Ad26.COV2.S COVID-19 vaccine was granted emergency use authorization in the US and (conditional) marketing authorization in the European Union; in more than 50 other countries.…”
Section: Introductionmentioning
confidence: 99%